Diverged Plant Terpene Synthases Reroute the Carbocation Cyclization Path towards the Formation of Unprecedented 6/11/5 and 6/6/7/5 Sesterterpene Scaffolds. Issue 5 (28th December 2017) - Huang, Ancheng C.; Hong, Young J.; Bond, Andrew D.; Tantillo, Dean J.; Osbourn, Anne
Abstract: Sesterterpenoids are a relatively rare class of plant terpenes. Sesterterpene synthase (STS)‐mediated cyclization of the linear C25 isoprenoid precursor geranylfarnesyl diphosphate (GFPP) defines sesterterpene scaffolds. So far only a very limited number of STSs have been characterized. The discovery of three new plant STSs is reported that produce a suite of sesterterpenes with unprecedented 6/11/5 and 6/6/7/5 fused ring systems when transiently co‐expressed with a GFPP synthase in Nicotiana benthamiana. Structural elucidation, feeding experiments, and quantum chemical calculations suggest that these STSs catalyze an unusual cyclization path involving reprotonation, intramolecular 1, 6 proton transfer, and concerted but asynchronous bicyclization events. The cyclization is diverted from those catalyzed by the characterized plant STSs by forming unified 15/5 bicyclic sesterterpene intermediates. Mutagenesis further revealed a conserved amino acid residue implicated in reprotonation. Abstract : Cyclizing to uncharted scaffolds : Terpene synthase (TPS)‐mediated cyclization defines the structures of terpene natural product scaffolds. Three diverged plant TPSs reroute carbocation cyclization towards formation of 6/11/5 and 6/6/7/5 scaffolds via de/re‐protonation, intramolecular proton transfer, and concerted but asynchronous double cyclization. A conserved amino acid residue implicated in reprotonation was identified.